Social media as a de/constructive learning environment for advanced EFL learners in the Algerian Educational System - BENAMOUR, MILOUD (My University, 2019)
Learning is regarded as a social activity; a student learns not only from the teacher and the curriculum or only in the classroom, but also from many other sources: technology, media, peers, colleagues and society in general. In an era of internet explosion, seeking for knowledge has become within the reach of everyone. As for social media and its role in the way we are learning today, with its multiple services and platforms, it has become an integral part of our daily lives, and therefore one major environment through which we learn different things. Today, social networking sites such as Facebook, Twitter and Instagram are known worldwide for playing important roles in education especially in the field of English as foreign language learning (EFL). Nowadays, online learning via social media is helping people to promote knowledge, where learners interact with each other. To understand how social media is helping learners to learn, this study investigates the use of social media as a constructive or destructive learning environment in EFL classes
Case of First Year Master Students of Language and Communication
Keywords: English as foreign language learning; Social media; Constructive learning environment